Demand and Supply of Skills in Ghana : How Can Training Programs Improve Employment? - Darvas, Peter; Palmer, Robert (Washington, DC: World Bank, 2014)
Ghana has a youthful population of 24 million and has shown impressive gains in economic growth and in poverty reduction over the last two decades. The necessary sustained growth requires three critical steps: (1) increase productivity in the strategic economic sectors, (2) diversify the economy, and (3) expand employment. Raising the level and range of skills in the country provides a key contribution to these core drivers of sustained growth. Skills development in Ghana encompasses foundational skills (literacy, numeracy), transferable and soft skills, and technical and vocational skills. These skills are acquired throughout life through formal education, training, and higher education; on the job through work experience and professional training; through family and community; and via the media. This report focuses on one segment of Ghana s skills development system: formal and informal technical and vocational education and training (TVET) at the pre-tertiary level. Although TVET alone does not guarantee productivity gains or job creation, it is generally agreed that a blend of cognitive, non-cognitive, intermediate, and higher technical skills is crucial to enhance the country s competitiveness and contribute to social inclusion, acceptable employment, and the alleviation of poverty. The public financing approach and general lack of incentives to improve TVET in Ghana help to perpetuate a supply-driven, low-quality skills system that responds very poorly to the needs of the economy, and especially its growth sectors. The national skills strategy should aim to complement, and be complemented by, reforms that are underway in related sectors (for example, private sector development and employment, the informal economy, information and communication technologies, and agriculture). One of the more innovative elements of the ongoing reform has been the establishment of sustainable financing for the skills development fund (SDF). Channeling the majority of TVET resources through a SDF will make it easier for funds to be allocated in line with general national socioeconomic priorities and specific priorities identified by Council for Technical and Vocational Education and Training (COTVET).